Evaluating the USA population's interest in sunscreen: a Google Trends analysis. (22nd December 2021) - Maghfour, J.; Boothby‐Shoemaker, W.; Lim, H. W.
Abstract : The use of a broad‐spectrum sunscreen remains an essential aspect of photoprotection. The environmental and health impacts attributed to certain ultraviolet filters have resulted in public confusion. Hence, the objective of this study is to explore public interest in sunscreen searches using Google Trends.